Meeting the challenges facing wheat production: The strategic research agenda of the Global Wheat Initiative - Langridge, Peter; Alaux, Michael; Almeida, Nuno Felipe; Ammar, Karim; Baum, Michael; Bekkaoui, Faouzi; Bentley, Alison R.; Beres, Brian L.; Berger, Bettina; Braun, Hans-Joachim; Brown-Guedira, Gina; Burt, Christopher James; et al. (MDPI, 2022)
Wheat occupies a special role in global food security since, in addition to providing 20% of our carbohydrates and protein, almost 25% of the global production is traded internationally. The importance of wheat for food security was recognised by the Chief Agricultural Scientists of the G20 group of countries when they endorsed the establishment of the Wheat Initiative in 2011. The Wheat Initiative was tasked with supporting the wheat research community by facilitating collaboration, information and resource sharing and helping to build the capacity to address challenges facing production in an increasingly variable environment. Many countries invest in wheat research. Innovations in wheat breeding and agronomy have delivered enormous gains over the past few decades, with the average global yield increasing from just over 1 tonne per hectare in the early 1960s to around 3.5 tonnes in the past decade. These gains are threatened by climate change, the rapidly rising financial and environmental costs of fertilizer, and pesticides, combined with declines in water availability for irrigation in many regions. The international wheat research community has worked to identify major opportunities to help ensure that global wheat production can meet demand. The outcomes of these discussions are presented in this paper.